PATIENT AWARENESS AND PERCEIVED HEALTH RISKS OF DIAGNOSTIC RADIATION IN NORTHERN NIGERIA - Abdulrahman, Umaru; Goni, Fatima Umar; Ibrahim, Mohammed; Abdullahi, Shuaibu; Abdulrazaq, Bamanga; Tasiu, Isah (FUDMA Journal of Sciences, 2025)
Diagnostic imaging is essential in contemporary clinical practice, yet many patients have limited understanding of radiation exposure and its associated risks. Insufficient awareness may influence anxiety, informed consent quality and willingness to undergo necessary imaging procedures. This study assessed patients’ knowledge and perception of radiation exposure during diagnostic imaging at a Nigerian teaching hospital. A descriptive cross-sectional study was conducted at the radiology department of Ahmadu Bello University teaching hospital, Shika. A structured, self-administered questionnaire was distributed to 210 patients undergoing diagnostic imaging. The questionnaire assessed demographic information, knowledge of radiation, perception of radiation effects, sources of information, and previous experiences with diagnostic imaging. Data were analysed using descriptive and inferential statistics. Overall awareness of radiation was low, with many respondents unable to correctly identify which imaging modalities use ionising radiation. Misconceptions were widespread, including the erroneous belief that ultrasound and MRI emit radiation. Knowledge of potential health risks was limited, and perceptions varied considerably across participants. Educational level demonstrated a significant association with radiation awareness, while many respondents reported never receiving radiation-related information from healthcare professionals, relying instead on informal sources such as family, friends or media. The study demonstrates substantial gaps in patient knowledge and perception of diagnostic radiation exposure. Improved communication within radiology departments is required, including structured counselling, simple educational materials and enhanced engagement by radiographers. Strengthening patient education may reduce misconceptions, support informed decision-making and promote safer use of diagnostic imaging services.